ANALYSIS OF LANGUAGE POLICY IN THE SOCIAL INTERACTIONS OF PONDOK PESANTREN DARUL MA'ARIF KAPLONGAN - Wa’adi, Akhmad; Subaweh, Ahmad Maskur; Muthmainnah, Fithry (Transpublika Publisher, 2024)
This study analyzes linguistic politeness in social interactions at Darul Ma'arif Kaplongan Islamic Boarding School, Indramayu, using a qualitative descriptive approach. The objectives are to identify forms of linguistic politeness, analyze influencing factors, and evaluate its impact on the quality of social interactions in the Islamic boarding school environment. Data collection methods include participant observation, in-depth interviews, documentation, and focus group discussions, with analysis using the interactive model of Miles, Huberman, and Saldana. Results show dominant forms of linguistic politeness include the use of Krama Inggil Javanese, polite second-person pronouns, controlled intonation and voice volume, and religious expressions. Influencing factors include social hierarchy, Islamic values, students' cultural backgrounds, and school rules. Linguistic politeness implications include character formation, social relationship harmonization, increased learning effectiveness, and preservation of traditional values. In conclusion, linguistic politeness in Islamic boarding school environment functions not only as a communication tool but also as a means of character education, tradition preservation, and creation of a harmonious social environment. This research provides important insights into the role of linguistic politeness in the context of traditional Islamic education.